Discriminatory attitudes and practices related to HIV/AIDS among healthcare personnel, and stigmatization of people living with HIV/AIDS / Saguntala Selvamani - Saguntala, Selvamani (2019)
Stigma and discrimination towards HIV/AIDS remain to be a challenge. In addition to distressing the lives of people living with HIV/AIDS, stigma is also causing hurdles to the progress and application of HIV prevention, treatment, care and support programmes. This research studies the discriminatory attitudes and practices related to HIV/AIDS from the perspectives of professional healthcare personnel and people living with HIV/AIDS. It assesses the factors associated with professional healthcare personnel’s discriminatory attitudes and their practices related to HIV, as well as investigates the enacted stigma among HIV-positive individuals in healthcare settings. This is a cross-sectional study comprising two parts. It was conducted between early August 2016 and April 2017 at the Federal Territory of Kuala Lumpur. The first part of the study was conducted among professional healthcare personnel (doctors) from public tertiary hospitals and four district health offices in Kuala Lumpur. This study was conducted among 370 doctors, using the universal sampling method. Meanwhile, the second part of the study was conducted among 282 people living with HIV (PLHIV) from two non-governmental organizations based in Kuala Lumpur using the self- administered method. Univariate and multiple logistic regression analyses were performed to analyse the data. In the first part of the study, 51.6% of the healthcare personnel admitted to having discriminatory attitudes and 53.8% of them acknowledged having poor practices while caring or treating PLHIV. Value-driven stigma was a strong determinant of discriminatory attitudes towards HIV/AIDS among healthcare personnel. Meanwhile, healthcare personnel who have perceived risk, have value-driven stigma and observed their colleagues being discriminative towards HIV-positive patients were two times more likely to have poor practices related to HIV/AIDS compared to those with no stigmatizing behaviour. In the second part of the study, the mean age of people living with HIV was 36.7 years. Gender wise, 83.7% of the participants were male, 11% iv female and 5.3% were transgender. The majority stated that HIV transmission were through sex with man who was HIV-positive (48.6%), followed by sex with woman who was HIV-positive (27%), shared needle with HIV-positive person (11.7%) and 14.2% of the participants refused to answer this question. In the multivariate analysis, the final result for the second part study showed that PLHIV with low levels of stigma were two times more likely to have good general healthcare seeking behaviour compared to those who have experienced higher stigmatization in healthcare settings. Stigma and discrimination among healthcare personnel in urban Malaysian healthcare settings appear to be driven primarily by perceived risk towards the illness, negative feelings as well as being judgemental towards PLHIV and experience of observing discriminatory behaviour by other colleagues. All this leads to discriminative behaviour and practices among the healthcare personnel. Hence, stigma reduction interventions are urgently needed to target these misconceptions and improve interactions with PLHIV. The application of this study can be used to provide a better quality of care and life for the people living with HIV/AIDS.